Integrated Analysis and Finding Reveal Anti–Liver Cancer Targets and Mechanisms of Pachyman (Poria cocos Polysaccharides) - Qin, Li; Huang, Dongning; Huang, Jian; Qin, Fuhui; Huang, Haixin (Frontiers in Pharmacology, 2021)
Our bioinformatics study aimed to characterize and certify crucial anti-cancer targets, functional processes, molecular mechanisms of Pachyman treating hepatocellular carcinoma (HCC) by utilizing pharmacology network and molecular docking analyses, experimental validation. The crucial anti-HCC targets of Pachyman were identified, including ALB, VEGFA, TNF, CASP3, SRC, EGF, CXCR4, STAT3, HRAS, HSP90AA1, MMP9, BCL2L1, FGF2, PTPRC, respectively. In addition, the correlative networks of all crucial biotargets of Pachyman to treat HCC were created accordingly. Functionally, these crucial genes were correlated with angiogenesis and neoplastic metastasis of HCC. Interestingly, the molecular docking findings indicated that ALB, VEGFA in HCC might be potent pharmacological targets of Pachyman. In experimental validation, the clinical samples of HCC showed reduced ALB protein expression and increased VEGFA protein level. Following Pachyman treatments in vitro, the intracellular level of ALB protein was elevated, while the cellular content of VEGFA protein was down-regulated. Taken together, current bioinformatics findings based on pharmacology network, molecular docking analyses elucidate the detailed molecular targets and signaling mechanisms of Pachyman to treat HCC. Interestingly, validated biotargets of ALB, VEGFA may be main potential biomarkers of detecting HCC medically.